Pengaruh Penyaluran ZIS, PDRB, dan Pengangguran terhadap Indeks Pembangunan Manusia dengan Kemiskinan sebagai Variabel Intervening - Nurhasanah, Ai; Suryanto, Asep; Friantoro, Dian (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
The Human Development Index (HDI) is an important indicator to measure the level of human welfare in a region. The purpose of this study was to determine the effect of ZIS fund, GRDP and unemployment on the Human Development index in West Java province with poverty as an intervening variable. This study uses a correlational method with a quantitative approach with secondary data obtained from BAZNAS, BPS and Open data West Java. The data used is panel data, namely a combination of time series data from 2017-2021 and cross section data of 27 cities. The data analysis method in this study uses panel data regression and path analysis. The analysis tool uses Eviews with the selected regression is the fixed effect model. The results showed that the variable distribution of ZIS funds had a positive and significant effect on poverty, while GRDP had a negative and significant effect on poverty and unemployment had a positive and significant effect on poverty. Then poverty has a negative effect on the Human Development Index, while the distribution of ZIS funds, GRDP and Unemployment has a positive effect on the Human Development Index. Then the distribution of ZIS funds, GRDP and unemployment affect the Human Development Index through poverty.